Jan Kochanowski’s Psalter – a Source of Polish Poetry and Mirror of the Human Mind - Buszewicz, Elwira (The Biblical Annals, 2023)
The article deals with Jan Kochanowski’s Psałterz Dawidów [David’s Psalter], published in 1579. This paraphrase of the biblical Psalter, intensely lyrical in its spirit, was inspired by George Buchanan’s Latin poetic paraphrase of the Psalms, which is strongly Horatianising. Kochanowski’s work can be seen as a presentation of humanist piety. That is to say that the borders between secular and sacred spaces, or even between Judeo-Christian and Pagan traditions, may seem blurred. The Psalter is also interconfessional (or “doctrinally neutral”) and acts as a universal mirror reflecting the human mind. The author analyses three of Kochanowski’s Psalms to demonstrate the intellectual and emotional space of his Psalter and its polyphonic structure: 1 (Beatus vir qui non abiit in consilio impiorum), 19 (Caeli enarrant gloriam Dei) and 91 (Qui habitat in adiutorio Altissimi), displaying some interplays of ideas and different approaches to paraphrasing applied by the poet.